L4 Sustained and strong HTT silencing by AAV5-miHTT as therapy for huntington's disease. (13th September 2016) - Evers, Melvin; Miniarikova, Jana; Blits, Bas; Spronck, Lisa; Brouwers, Cynthia; Déglon, Nicole; Motlik, Jan; Bankiewicz, Krystof; Southwell, Amber; Haan, Martin de; Richard, Charles; Petry, Harald; et al.
Abstract : Huntington's disease (HD) is an autosomal dominant neurodegenerative disorder caused by a CAG trinucleotide repeat expansion in the first exon of the HTT gene. This CAG repeat expansion results in an expanded polyglutamine repeat in the huntingtin (HTT) protein, causing toxic gain-of-function and affecting numerous cellular processes. Lowering the expression of mutant HTT (gene silencing) and thereby reducing downstream toxic effects is hypothesised to be therapeutically beneficial. Gene therapy using viral vectors can induce long-term HTT silencing following single administration. The gene silencing therapy developed by uniQure is based on a microRNA targeting human HTT (miHTT). The DNA expression cassette encoding the miHTT is delivered to the cell using adeno-associated viral vector serotype 5 (AAV5-miHTT). After a thorough selection process, the therapeutic lead candidate AAV5-miHTT has been identified that induces strong and safe HTT silencing in vivo. Proof-of-concept (PoC) studies have shown that local injection of AAV5-miHTT in the striatum of a lentiviral HD rat model resulted in reduced number of HTT aggregates and subsequently prevention of striatal neuronal dysfunction. In the humanised (Hu)128/21 mouse model sustained target engagement was shown with up to 80% HTT silencing seven months post intra-striatal injection. No acute toxicity of AAV5-miHTT has been observed thus far, nor were deleterious effects of HTT silencing shown up to seven months post-treatment in Hu18/18 control mice. Currently, long-term therapeutic PoC studies to examine mitigation of HD phenotype after AAV5-miHTT administration are ongoing in various rodent HD models and transgenic HD mini pigs. To determine route of delivery in large brain, AAV5-GFP has been administered into the central nervous system of control mini pigs and non-human primates (NHP). Administration of AAV5-GFP into the putamen and thalamus showed widespread distribution of the vector in the caudate nucleus, putamen, globus pallidus and cortex. At present, efficacy, safety and tolerability of AAV5-miHTT are being evaluated in NHPs. The combination of widespread vector distribution, great target engagement, long-term expression and good safety profile allowed us to select AAV5-miHTT as lead candidate for HD gene therapy development.